2005
DOI: 10.1080/02640410410001730197
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity intermittent running and field hockey skill performance in the heat

Abstract: higher. Estimated mean ± x s sweat rate of 1.27 ± 0.10 l.h -1 was greater in the hot trial than the 1.05 ± 0.12 l.h -1 in the moderate trial (P<0.05). Body mass was well maintained in both trials. No difference in serum cortisol, blood lactate, plasma volume and plasma ammonia concentrations were found. These results demonstrate that field hockey skill performance is decreased following intermittent, high intensity shuttle running and that this decrease is greater in hot environmental conditions. The exact mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
1
37
2
Order By: Relevance
“…In contrast to the present study, other studies using the LIST have shown a deterioration in sprint performance as the number of sprints performed increased in trained (Sunderland and Nevill 2005) and youth (Phillips et al 2010) game players. The decline in sprint times in those studies ([0.09 s) are higher than the maximum shown by the elites (?0.02) and non-elites (?0.09), which may explain some of the differences.…”
Section: Discussioncontrasting
confidence: 84%
“…In contrast to the present study, other studies using the LIST have shown a deterioration in sprint performance as the number of sprints performed increased in trained (Sunderland and Nevill 2005) and youth (Phillips et al 2010) game players. The decline in sprint times in those studies ([0.09 s) are higher than the maximum shown by the elites (?0.02) and non-elites (?0.09), which may explain some of the differences.…”
Section: Discussioncontrasting
confidence: 84%
“…Recently, attention has been afforded to addressing the utility of the MSSRT (and other runningbased tests) as markers of sport-specific endurance performance, rather than _ VO 2 max (e.g. Aziz et al 2005a, b;Lemmink et al 2004a, b;Sunderland and Nevill 2005). In the manner of the present study, Aziz et al (2005a) calculated the total number of shuttles completed by their sample of 16 male athletes and games players, referring to it as their 'performance indicator'.…”
Section: Discussionmentioning
confidence: 99%
“…6 Besides, body water loss could be associated with the intensity, duration, proprieties and quantity of the outfits used during the practice. 2 In this view, even though studies challenge its efficacy in some occasions, 7 the high-intensity training in treadmill 8 bicycle 9 and using the body´s weight 10,11 has been used with the objective to improve levels of physical fitness as well as health, due to its superiority in relation to moderate exercises. [12][13][14] Nonetheless, studies using the HIIT approach and its effects on sweating and hydration rates are still non conclusive in the literature.…”
Section: Introductionmentioning
confidence: 99%